VISUALIZING ECO SPIRITUALITY IN GIFT IN GREEN - Thomas, Deepthi; S, Selvalakshmi; S, Shanthi Shenoy (ShodhKosh: Journal of Visual and Performing Arts, 2026)
"Eco-Spiritual exploration of Gift in Green" examines how spiritual awareness and ecological consciousness interact profoundly in Sarah Joseph's well-known book Gift in Green. This article provides a systematic examination of Sarah Joseph's eco-spiritual vision, revealing its many facets and ramifications. The book presents a comprehensive understanding of humans and nature by fusing environmental stewardship, respect for nature, and an understanding of the interdependence of all living things. Sarah Joseph invites readers to consider their relationship with nature and their place in the ecological order through her masterful characterization and evocative storytelling techniques. In light of the third millennium's environmental challenges, the study article investigates the effectiveness of Eco spirituality in promoting a deeper sense of connectedness to nature. Joseph's story promotes a more peaceful and sustainable way of living by integrating ecology and spirituality. The study also examines how Joseph's literary portrayal of eco-conscious life has contributed to environmental advocacy and broader cultural conversation. In the end, "Exploring Eco Spirituality: Insights from Gift in Green by Sarah Joseph" takes readers on a spiritual and ecological journey while illuminating the transforming potential of eco spirituality as a catalyst for individual and societal awakening. Additionally, by analysing the rich environmental imagery, sensory descriptions, and symbolic landscapes that influence the novel's artistic vision, the paper aesthetically visualizes Eco spirituality. Rivers, paddy fields, rain, birds, and the verdant village setting are all transformed by Sarah Joseph into hallowed aesthetic landscapes that arouse readers' emotions and spirituality. Nature in Gift in Green is not only a backdrop but also a living presence rich with beauty, rhythm, and heavenly force. By allowing readers to experience nature via awe, empathy, and spiritual reflection, the artistic depiction of the environment enhances ecological consciousness. As a result, the book shows how literary beauty may develop into a potent tool for fostering ecological awareness and spiritual harmony between people and the natural world.